Is Privatization Working in Ukraine? New Estimates from Comprehensive Manufacturing Firm Data, 1989-2013 - J. David Brown; John S. Earle; Solomiya Shpak; Volodymyr Vakhitov (Institute for the Study of Labor (IZA), 2015)
This paper estimates the relative multi-factor productivity (MFP) of privatized and state-owned enterprises using a long panel on all initially state-owned manufacturing firms in Ukraine. The large size and length of the time series in the data permit us to track the privatization process and to estimate the impact of privatization within industry-year cells and with controls for firm fixed effects and trends. Results with these methods imply an average 5-10% relative MFP for majority privatized versus state-owned firms. The gap increases with time since privatization, reaching about 15-17% five years after privatization. It also increases with calendar time although recent privatizations are associated with smaller relative MFP. We find no evidence of "sequencing" of privatization based on 1992 relative MFP, but the data suggest a higher survival rate for privatized versus state firms and one that is more closely linked to 1992 MFP. The results also imply that MFP gains from privatization are decreasing in pre-privatization MFP. The relatively few cases in which foreign investors take control result in much higher relative MFP, 22-40% on average, compared to domestic private ownership, but the gap is much lower when the foreign source country is "offshore" an indirect channel for Ukrainian nationals and it is also lower when the source is Russia. Privatization of 100% ownership has much larger effects than partial privatization of either minority or majority stakes, ownership structures that have largely disappeared since the early 2000s, as Ukraine has sold off remaining shares. Nevertheless, our database contains more than 1000 majority state-owned manufacturing firms as of 2013 that could be considered for privatization in the future.
Keywords: D24; G34; L33; P31; 330; productivity; privatization; selection bias; foreign ownership; Ukraine